A Need Analysis on English Teaching Materials for Midwifery Department Students at the Muslim University of Indonesia (UMI) - Jibran, Ahmad Ari; Samtidar, Samtidar; Abduh, Amirullah (Celebes Journal of Language Studies, 2024)
There are two research objectives in this research, they are to find out the target needs of the Midwifery department at the Muslim University of Indonesia (UMI); and to find out the obstacles faced by the students of midwifery department of Muslim University of Indonesia (UMI) in learning English. The research design is mixed-method research. There was 1 lecturer and 27 students at the Muslim University of Indonesia (UMI) that was taken as the subject of the research. The researcher used a questionnaire as the research instrument. The result of the research revealed that emphasizing midwifery terminology, effective communication skills, and written proficiency, the findings underscore the necessity of adjusted English language education for this group. Challenges identified include difficulties in vocabulary acquisition, comprehension, pronunciation, and confidence in speaking and writing. Addressing these obstacles requires targeted interventions such as refined instructional methods, confidence-building measures, vocabulary-focused interventions, and effective reading strategies. These findings align with the theory's emphasis on understanding learners' needs and implementing tailored solutions to facilitate language acquisition.